2017
DOI: 10.1259/bjrcr.20150519
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic spindle cell sarcoma (PSCS) (formerly known as malignant fibrous histiocytoma, MFH) of the spleen, mimics an atypical haemangioma on99mTc-RBC, CT and Ultrasound: staging with18F-FDG PET/CT

Abstract: A 63-year-old male was found to have a 7.5-cm splenic mass that had imaging appearances of an atypical haemangioma on CT, ultrasound and a 99mTc-RBC scan, and he was followed conservatively with serial ultrasounds. Sixteen months later, however, the splenic lesion grew and he developed numerous new liver masses which were biopsy confirmed to be a pleomorphic spindle cell sarcoma (PSCS), formerly known as malignant fibrous histiocytoma (MFH). A staging 18F-FDG PET/CT was performed and showed innumerable, mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In three cases, the patients presented with splenic rupture associated with haemodynamic compromise [ 28 , 30 , 40 ]. The subject case also presented with a non-specific one-week history of abdominal pain without associated symptomatology or biochemical manifestations [ 7 , 10 , 14 , 17 , 19 , 22 , 25 27 , 30 , 33 , 35 , 37 , 38 , 41 , 42 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…In three cases, the patients presented with splenic rupture associated with haemodynamic compromise [ 28 , 30 , 40 ]. The subject case also presented with a non-specific one-week history of abdominal pain without associated symptomatology or biochemical manifestations [ 7 , 10 , 14 , 17 , 19 , 22 , 25 27 , 30 , 33 , 35 , 37 , 38 , 41 , 42 ].…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…Prior literature showed that UPS is FDG avid on FDG-PET/CT, [ 33 35 ] which appears to apply to splenic UPS as well. [ 27 ] CT findings as mentioned above may be useful to avoid delaying radical surgery early in the splenic UPS disease course.…”
Section: Discussionmentioning
confidence: 99%
“…Although a specific antibody for UPS has not been identified, vimentin, CD68, α-SMA and α-antichymotorypsin were often positive in the previous studies (Table 1) . [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] Immunohistochemistry may be useful for ruling out specific known lines of differentiation. Splenectomy is the most radical therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations